Parasitoids of the Australian citrus whitefly, Orchamoplatus citri (Takahashi) (Hemiptera, Aleyrodidae), with description of a new Eretmocerus species (Hymenoptera, Aphelinidae) - Schmidt, Stefan; de Barro, Paul; Jamieson, Lisa (Zootaxa, 2011)
A field survey for potential biological control agents of the Australian citrus whitefly, Orchamoplatus citri (Takahashi), resulted in the discovery of three species of chalcid parasitoids (Hymenoptera, Chalcidoidea), viz.: Cales orchamoplati Viggiani & Carver, a species belonging to a genus that is currently unplaced to family within Chalcidoidea, and two species of Aphelinidae, Encarsia iris (Girault) and Eretmocerus orchamoplati sp. nov. Orchamoplatus citri is the first host record for E. iris. Morphological diagnoses are given, and DNA sequence data of the 28S rDNA and the cytochrome oxidase I genes are provided to define species at the molecular level.